Synthesis and α-Glucosidase Inhibitory Mechanisms of Bis(2,3-dibromo-4,5-dihydroxybenzyl) Ether, a Potential Marine Bromophenol α-Glucosidase Inhibitor - Liu, Ming (Molecular Diversity Preservation International, 2011)
Bis(2,3-dibromo-4,5-dihydroxybenzyl) ether (BDDE), derived from the marine algae, is a potential α-glucosidase inhibitor for type 2 diabetes treatment. In the present study, a synthetic route was established as a valid approach to obtain BDDE. Fluorescence spectra, circular dichroism spectra and molecular docking methods were employed to elucidate the inhibitory mechanisms of BDDE against α-glucosidase. The results showed that BDDE could be prepared effectively and efficiently with the established synthetic methods. Synthetic BDDE bound with α-glucosidase and induced minor conformational changes of the enzyme. The docking results indicated the interaction between BDDE and α-glucosidase was driven by both hydrophobic forces and hydrogen bonds. The docked BDDE molecule was completely buried in the α-glucosidase binding pocket with part of the molecule reaching the catalytic center and overlapping with the position of glucose, and the rest of the molecule extending towards protein surface. This study provides useful information for the understanding of the BDDE-α-glucosidase interaction and for the development of novel α-glucosidase inhibitors.